2021
DOI: 10.1021/acs.jpcb.1c06899
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Structures of Amorphous Solid Water

Abstract: High-energy X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) of amorphous solid water (ASW) were studied during vapor deposition and the heating process. From the diffraction patterns, the oxygen–oxygen pair distribution functions (PDFs) were calculated up to the eighth coordination shell and an r = 23 Å . The PDF of ASW obtained both during vapor deposition at 80 K as well as the subsequent heating are consistent with that of low-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Most importantly, the peak position and fwhm of the derived LDA are identical to ASW, as also visible in Figure S4. This is consistent with X-ray and neutron data, demonstrating that ASW is a structural analogue to LDA. , This finding is in contrast to work by Kolesnikov et al, who observed considerable differences between the vapor deposits and the LDA obtained from HDA. The difference in their study might actually be due to the microporous nature of ASW, resulting in many molecules that are not tetrahedrally coordinated, as compared to the compact nature and perfect tetrahedral coordination in LDA.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Most importantly, the peak position and fwhm of the derived LDA are identical to ASW, as also visible in Figure S4. This is consistent with X-ray and neutron data, demonstrating that ASW is a structural analogue to LDA. , This finding is in contrast to work by Kolesnikov et al, who observed considerable differences between the vapor deposits and the LDA obtained from HDA. The difference in their study might actually be due to the microporous nature of ASW, resulting in many molecules that are not tetrahedrally coordinated, as compared to the compact nature and perfect tetrahedral coordination in LDA.…”
supporting
confidence: 90%
“…How do the vibrational modes of the so-derived LDA and crystalline ice compare to vapor-deposited amorphous solid water (ASW) and other crystalline ices? A comparison of the different states and references ( 30 ), ( 33 ), ( 51 ), and ( 52 ) of ice Ih and amorphous solid water (ASW) is given in Table 1 . Most importantly, the peak position and fwhm of the derived LDA are identical to ASW, as also visible in Figure S4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the O−H stretching region (Figure S5a), no significant changes were noticed, but in the dangling O−H region, the peak at 3667 cm −1 disappeared upon the formation of CH (Figure S5b), which suggested the collapse of micropores in ASW. 45,46 To see the temperature dependency of CH Formation, we annealed the ethane/H 2 O (1:1) ice mixture at 55 K for 18 h. We did not observe any peak arising at 2982 cm −1 (Figure S6). Hence, we concluded that CH formation of ethane in UHV at cryogenic temperatures depends significantly on the temperature and annealing time.…”
Section: ■ Results and Discussionmentioning
confidence: 96%